IN-SILICO ANALYSIS OF THE INTERACTION BETWEEN D7 PROTEIN FROM THE SALIVARY GLAND OF Ae. albopictus AND Thromboxane A2 FOR DEVELOPING ANTIPLATELET AGENT - Syubbanul Wathon; Kartika Senjarini; Rike Oktarianti; Asmoro Lelono (BRIN - Badan Riset dan Inovasi Nasional, 2025)
The salivary glands of mosquito vector diseases contain various biological components which facilitate blood-feeding into the host's body. These components are mostly protein molecules. Numerous protein molecules in the salivary glands have gained substantial research emphasis to determine their role and function, including those in the salivary glands of Ae. albopictus. D7 protein is the main component in Aedes salivary glands, which aids in inhibiting platelet aggregation by binding to the Thromboxane A2 (TxA2) during the blood-feeding. TxA2 is a eicosanoid molecule that stimulates platelet aggregation. The protein's ability to bind TxA2 shows that this protein has potential as a new antiplatelet agent. The examination of the D7 protein in binding TxA2 was performed through an in-silico approach using the molecular docking method. This research included selecting the 3D model of the D7 protein and the TxA2 ligand, preparing the 3D model of the D7 protein, native ligands, and test ligands, targeted molecular docking method, validating the molecular docking, analysis and visualization of the docking results. The molecular docking validation shows an RMSD value of 1.657 Å. The results of molecular docking show an ΔG value of -5.60 kcal/mol, meaning that the D7 protein can bind to the TxA2 ligand stably and spontaneously. The active site of the D7 protein in binding the TxA2 ligand consists of several amino acid residues, namely THR 190, GLU 268, TYR 178, PHE 154, ILE 175, ARG176, VAL 293, TYR 248, and TYR 178. The ability of D7 protein to bind TxA2 as an inducer of platelet aggregation has demonstrated its potential as a novel antiplatelet agent. These results can pave further development of drug discovery in the medical and pharmaceutical fields.